Evolution mechanism of rapid solidification microstructure of an undercooled copper-based single phase alloy - Wenhua Du; Kai Hou; Xuguang Xu; Ismal Saad; Willey Liew Yun Hsien; AN Hongen; Nancy Julius Siambun; Bih-Lii Chuab; Wang Hongfu (Journal of Materials Research and Technology, 2024)
Using undercooling technology combined with melt purification of glass and recirculation overheating, different undercoolings were successfully obtained for Cu60Ni38Co2 alloy samples. Applying high speed photography technique, the physical process of undercooled solidification was observed and relationship between undercooling and solidification rate was analyzed. Experimental results indicate the critical undercoolings exist in the structure evolution process. Electron backscatter diffraction (EBSD) analysis was applied to characterize the Cu60Ni38Co2 alloy sample with a maximum undercooling of 255K, revealing grain orientation and the corresponding orientation difference distribution. In addition, transmission electron microscopy (TEM) showed high density dislocation networks. Combining EBSD and TEM data analysis, an important conclusion was drawn: recrystallization is the main factor for grain refinement at high undercooling. This finding is of great significance for a deeper understanding of the structure evolution in the physical process of undercooled alloys.